Violation of Marriage Age Limit Provisions in Indonesia: Counseling and Education Perspectives - Suryadi, Suryadi; Mursalim; Anisah Prafitralia (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Violation of the marriage age limit provisions is a complex issue and is often overlooked in the context of society. This study aims to explore violations of the marriage age limit from the perspective of counseling and education. In this study, the author employs a qualitative methodology with a descriptive approach, utilizing data collection techniques that include observation, documentation, and interviews, and data analysis based on the theory of Miles and Huberman. In this study, the author analyzes the factors that encourage violations, including social norms, economic pressures, and a lack of understanding of the long-term impacts of early marriage. Through a counseling approach, it is hoped that individuals and families can be given a better understanding of the importance of a healthy marriage age limit. In addition, education plays a crucial role in disseminating information and increasing public awareness of the risks and consequences of marriages that are not in accordance with the provisions. Additionally, early marriage can also impact the quality of education received by teenagers. They may not have equal access to quality education programs, or they may not have enough time to focus on their education. This study is expected to contribute to the development of more effective policies, education, and counseling programs that can reduce violations of the marriage age limit in society. Keywords: early marriage, marriage dispensation, marriage age limit, reproductive health